A Community-Based Music Therapy Support Group for People With Alzheimer's Disease and Their Caregivers: A Sustainable Partnership Model - Rio, Robin (Frontiers in Medicine, 2018)
People with Alzheimer's and related dementias and their family caregivers who reside at home have unique strengths and needs. They have the strengths of being in a place with which they are familiar, with people whom they are in close relationship. Often it is the spouse who provides the primary care of their loved one, and as the disease progresses both members of the couple are at risk for depression, isolation, and decreased contact with peers and community networks that serve to help maintain sociocultural, intellectual, physical, sensory, and spiritual needs. The person with Alzheimer's Disease (AD) loses life skills and sense of self as their memory loss worsens, and the caregiver-loved one, whether they are the spouse, relative, or close companion, becomes increasingly burdened physically and emotionally. Meaningful support through a community-based peer group helps meet the needs of the person with dementia and their caregiver from the first symptoms to the later stages of AD, through a carefully designed music therapy program tailored to preferences, culture, and ability. The music therapist working in the community provides practical leadership in coordination with local agencies, understands the needs of the person with dementia and their caregiver from a cultural and psychosocial perspective, and is creatively equipped in all facets of musical engagement for health and wellness, and fosters cognitive/intellectual, socio-emotional, physical, and spiritual support. The MT support group was found to relieve some of the strain on caregivers by allowing for greater emotional support through relationships with peers and professionals, and through the increase of meaningful interactions with their loved one with dementia. Through enjoyment of shared, pleasurable music experiences that stimulate memories, movement, language, and socialization, the person with AD and their caregiver developed a deeper connection with each other, and gained support, creative expression, and comfort from their peer group, as well as practical networking and sharing of resources and information related to their specific health and wellness needs. The community-based MT support group has been replicated twice within the region, and is a promising model for other communities. Formal research is recommended to provide further evidence of the effectiveness of the approach, and to allow for greater accessibility for marginalized people to participate in a program such as this in their own community.